Mycobacterium avium subspecies paratuberculosis detection in beef cattle in Taman Pertanian Universiti, UPM - Ismail, Nur Farah Athirah (2016)
Mycobacterium avium subspecies paratuberculosis(MAP) is the aetiology agent causes Johne‟s disease which viewed as a chronic, contagious bacterial of intestinal tract in ruminant species. The infection that caused substantial losses to the farmer was characterized by chronic or intermittent diarrhoea, progressive weight loss, and decreased production. This study was conducted to determine the presence of MAP antigen and antibodies in the faeces and serum, respectively, in the cattle. A total of 213 faecal samples and 71 serum samples were collected from 71 cattle at Taman PertanianUniversiti (TPU), Universiti Putra Malaysia (UPM). These samples were tested using Ziehl-Neelsen acid-fast stain method for antigen detection and complement fixation test (CFT) for antibodies detection. Ziehl-Neelsen staining revealed that 60 (28.2%) of 213 samples were positive for M. avium antigen while, CFT revealed 3 (4.2%) of 71 serum samples were positive for the antibody. However, MAP is not the only acid fast organism; thus the determination of species of the organismshould supported by faecal culture. In conclusion, this study showed that there is MAP infection in the cattle herd at TPU, UPM, with the presence of antigen causing agent and antibodies in faecal and serum samples, respectively, of cattle.